Selected determinants of nutritional behaviours among professional athletes performing team sports - Gacek, M. (Національний технічний університет "Харківський політехнічний інститут", 2019)
The aim of the study was to evaluate the relationship between sex and experience in professional sports experience of athletes performing team sports. The study was carried out in a group of 518 Polish athletes (252 women and 266 men) aged 19 to 33, with professional sports experience between 3 and 21 years (median: 11). An original questionnaire concerning nutritional habits was used in the study, drawing on the qualitative recommendations of the Swiss food pyramid for athletes. Statistical analyses were carried out using logistic regression in the PQStat package ver. 1.6. Statistical analysis demonstrated that women significantly more often ate vegetables and limited animal fats, fast food and sweetened carbonated drinks, whereas men significantly more often preferred mineral water and consumed their meals regularly (p<0.05). Along with professional sports experience, the participants improved their fluid replacement during exercise and the regularity of meals, while fruit and vegetables consumption decreased (p<0.05). The predictive role of sex and professional sports experience for certain eating habits of Polish athletes playing team sports was demonstrated.
Keywords: eating habits; athletes; team sports; sex; professional sports experience